MR of the base of the pons in Wilson disease. - Imiya, M; Ichikawa, K; Matsushima, H; Kageyama, Y; Fujioka, A (American Journal of Neuroradiology, 1992)
The authors describe unusual MR findings in three patients with Wilson disease, eg, white matter changes in the base of the pons, and speculate whether the changes are caused by Wilson disease or by concomitant disease, and whether the pontine lesions they observed are primary or related to lesions located more rostrally.